Effects of rare earth Ce doping on the structure and photocatalytic performance of ZnO - Yu, C.; Yang, K.; Yu, J.; Peng, P.; Cao, F.; Li, Xin Yong; Zhou, X. (2011)
A series of ZnO photocatalysts doped with different amounts of cerium were prepared by co-precipitation and then calcined at different temperatures. The prepared pure ZnO and Ce-doped ZnO samples were characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), UV-visible (UV-Vis) spectroscopy, and photoluminescence (PL) spectroscopy. The photocatalytic activity of the samples was evaluated by the photodegradation of acid orange II under UV light (?=365 nm) irradiation. FT-IR results showed that ZnO doped with 2% (w, mass fraction) cerium had far more OH groups over the surface of the doped sample than the pure ZnO. At the same time, PL tests indicated that the presence of 2% (w) cerium effectively suppressed the recombination of the photogenerated hole-electron pairs. On the other hand, the calcination temperatures influenced the crystallinity and crystal size of the catalysts. XRD tests indicated that the sample calcined at 500 °C had good crystallinity and a small crystal size while elevated temperature treatment (600-800 °C) would result in sintering and increase the crystal size. At the optimal calcination temperature of 500 °C and at 2% (w) cerium doping the composite photocatalyst had much higher photocatalytic activity and stability compared with pure ZnO. The high photocatalytic performance of the Ce doped ZnO could be attributed to an increase in surface OH groups, high crystallinity and a low recombination rate of electron/hole (e-/h+) pairs. © Editorial office of Acta Physico-Chimica Sinica.